Changes in the gingival margin after crown lengthening in patients with altered passive dental eruption type IB - Molano, Pablo; Domínguez, Leidy; Erazo, Diana (Revista Estomatología, 2011)
Objectives: The purpose of this descriptive investigation is to evaluate the changes in the dental high 3 months after surgery including the more frequent complications after in patients with passive altered eruption type IB. Materials and methods: This study evaluated 20 patients with altered passive eruption type IB classified into group I (central incisors, lateral and canine 14 cases) and group II (first premolar, second premolar and first molar 6 cases), who have performed crown lengthening and assessed the change in tooth size before surgery, in the immediate postoperative and 3 months after surgery for each type of tooth. Results:It was found that gingival crown migration to central incisors and canines (group I) and first and second premolars (group II) was approximately 1 mm, for the first molar (group II) was of 0.65mm and 1.85mm lateral incisors being the tooth with more gingival regrowth. Postsurgical complications evaluated were the presence of extraoral swelling was higher in the cases in group I (60%), papillary and marginal inflammation mild (20%), moderate (50%) and severe (30%) of cases which was always higher in group I. Postsurgical pain was found in 80% of patients (16) patients which commonly was mild (60%) to moderate (40%). Only one case showed postsurgical bleeding (5%). Conclusions: After making a crown length surgery in patients with passive altered eruption there is a coronal migration of the gingiva in all teeth being bigger in the lateral incisor. The listed complications are : extraoral edema, pain and papillary inflammation. Key words: Crown Length, periodontal surgery, gingival margin, passive altered eruption 1B, periodontal surgery complications.